2021
DOI: 10.1186/s12877-021-02276-w
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia as a predictor of mortality among the critically ill in an intensive care unit: a systematic review and meta-analysis

Abstract: Background The evidence of sarcopenia based on CT-scan as an important prognostic factor for critically ill patients has not seen consistent results. To determine the impact of sarcopenia on mortality in critically ill patients, we performed a systematic review and meta-analysis to quantify the association between sarcopenia and mortality. Methods We searched studies from the literature of PubMed, EMBASE, and Cochrane Library from database inceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 62 publications
(92 reference statements)
2
45
2
3
Order By: Relevance
“…There was a statistically significant correlation between the length of ICU stay and the sarcopenic and non-sarcopenic groups in the study by Mohanty et al [16], whereas, in our study, no such correlation was associated. In a study by Zhang et al [17], age was found to be an important confounding factor, whereas, in our study, we did not have age as a confounding factor. Also, in addition, there were a number of important confounding factors, such as chronic obstructive pulmonary disease (COPD), obesity, and cardiac failure, which would have influenced sarcopenia's impact on mortality, whereas, in our study, no such confounding factors were observed.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…There was a statistically significant correlation between the length of ICU stay and the sarcopenic and non-sarcopenic groups in the study by Mohanty et al [16], whereas, in our study, no such correlation was associated. In a study by Zhang et al [17], age was found to be an important confounding factor, whereas, in our study, we did not have age as a confounding factor. Also, in addition, there were a number of important confounding factors, such as chronic obstructive pulmonary disease (COPD), obesity, and cardiac failure, which would have influenced sarcopenia's impact on mortality, whereas, in our study, no such confounding factors were observed.…”
Section: Discussioncontrasting
confidence: 82%
“…As far as gender is considered, sarcopenia is higher in women. Few studies had shown an estimated prevalence of 15.3% in men and 20.5% in women in a tertiary-care hospital [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the malnourished group had longer duration of MV than the normal nutritional status group (P < 0.05). As demonstrated by Jaitovich et al [13] and Weijs et al [14], low muscle mass is an independent risk factor for mortality in critically ill patients [15]. Thus, early identi cation of low muscle mass may lead to more timely nutritional support, which may bene t the prognosis of patients.…”
Section: Discussionmentioning
confidence: 94%
“…According to the literature, the complication rate of sarcopenia in ICU was 41%, and the hospital mortality of patients with sarcopenia was higher (OR= 2.28, P<0.001). 9 Finally, we planned to recruit no less than 148 patients (with a unilateral significance level of 0.05 and a beta risk of 0.20). In the beginning, we collected 274 patients (age>18 years old) diagnosed with SCAP and admitted to ICU between January 2019 and July 2021.…”
Section: Study Populationmentioning
confidence: 99%
“…As age increases, the continuous decline of muscle mass and loss of function could lead to falls, weakness, and even death. 8,9 As digital imaging develops, CT imaging of psoas area, paravertebral, appendix, and paraspinal muscle has become a reliable methodology for diagnosing sarcopenia. [10][11][12][13] The area of the psoas muscle was the most commonly used indicator for skeletal muscle mass.…”
Section: Introductionmentioning
confidence: 99%